Longitudinal Associations Between Healthcare Resources, Policy, and Firearm-Related Suicide and Homicide from 2012 to 2016 - Choi, Kristen R. (J Gen Intern Med, 2020)
BACKGROUND: Firearm-related violence is a leading cause of mortality in the United States (US). Prior research suggests that public policy plays a role in firearm mortality, but the role of healthcare resources (physicians, insurance coverage) within the US policy context has not yet been studied. OBJECTIVE: To examine how healthcare resources and social/firearm policy affect firearm-related suicide and homicide rates in the US. DESIGN: Longitudinal, ecological study. SETTING: US. PARTICIPANTS: US states from 2012 to 2016 (N = 242). MEASUREMENT: The outcome variables were age-adjusted, firearm-related suicide and homicide rates. Predictor variables were healthcare resources (physicians, Medicaid benefits generosity) and policy context (social policy, firearm policy) with covariates for sociodemographic factors. RESULTS: Healthcare provider variables did not have significant associations to firearm-related suicide or homicide. In fully saturated models, more worker protection laws, greater average population density, more alcohol regulation, and more firearm prohibition policies were associated with fewer firearm-related suicides. Higher generosity of Medicaid benefits was associated with fewer firearm-related homicides. Poverty rate was a predictor of both outcomes. LIMITATIONS: This state-level study cannot make individual-level inferences. Only proxy variables were available for measuring gun ownership and actual gun ownership rates may not have been ideally captured at the state level. CONCLUSIONS: At the state level, there are protective associations of certain social, healthcare, and firearm policies to firearm-related suicide and homicide rates. Healthcare resources play a role in population-level firearm outcomes but alone are not sufficient to decrease firearm-related homicide or suicide. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05613-3) contains supplementary material, which is available to authorized users.